2022
DOI: 10.1093/brain/awac285
|View full text |Cite
|
Sign up to set email alerts
|

Precuneus magnetic stimulation for Alzheimer’s disease: a randomized, sham-controlled trial

Abstract: Repetitive transcranial magnetic stimulation (rTMS) is emerging as a non-invasive therapeutic strategy in the battle against Alzheimer’s disease. Alzheimer’s disease patients primarily show alterations of the default mode network for which the precuneus is a key node. Here, we hypothesized that targeting the precuneus with TMS represents a promising strategy to slow down cognitive and functional decline in Alzheimer’s disease patients. We performed a randomized, double-blind, sham-controlled, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
89
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 53 publications
6
89
0
Order By: Relevance
“…Along the same lines, we have recently demonstrated that a 2‐week course of 20‐Hz rTMS over the PC improves long‐term memory in patients with AD, providing key preliminary evidence that PC stimulation is a viable strategy to improve cognitive dysfunction in AD 18 . This result has been recently confirmed by the first long‐term 24 weeks, phase II, randomized‐controlled trial in which we reported safety and efficacy of rTMS over the PC in reducing functional and cognitive decline in a sample of 50 patients with AD (NCT03778151) 47 . Hence, the current findings may be important for future studies to consider, as they can better stratify patients with AD and evaluate potential responses to therapy in the context of clinical applications based on neurostimulation.…”
Section: Discussionsupporting
confidence: 53%
“…Along the same lines, we have recently demonstrated that a 2‐week course of 20‐Hz rTMS over the PC improves long‐term memory in patients with AD, providing key preliminary evidence that PC stimulation is a viable strategy to improve cognitive dysfunction in AD 18 . This result has been recently confirmed by the first long‐term 24 weeks, phase II, randomized‐controlled trial in which we reported safety and efficacy of rTMS over the PC in reducing functional and cognitive decline in a sample of 50 patients with AD (NCT03778151) 47 . Hence, the current findings may be important for future studies to consider, as they can better stratify patients with AD and evaluate potential responses to therapy in the context of clinical applications based on neurostimulation.…”
Section: Discussionsupporting
confidence: 53%
“…This has clear implications for clinical trials that aim to enroll individuals with elevated amyloid, who have the highest likelihood of suffering cognitive decline during the trial. Future research should examine if connectivity of this circuit may facilitate interventions (Koch et al, 2022 ) and provide a biomarker for outcomes in cognitive remediation trials (Rajji et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, EEG-based band-specific connectivity analysis could be more useful than fMRI in identifying innovative targets for transcranial electrical and magnetic neuromodulation or focused ultrasound techniques (Stefani et al, 2022), which are increasingly showing value as symptomatic or also disease-modifying therapies in other neurodegenerative neurological diseases (Koch et al, 2022).…”
Section: Discussionmentioning
confidence: 99%